2020
DOI: 10.3352/jeehp.2020.17.19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multi-professional simulation-based training on perceptions of safety and preparedness among health workers caring for coronavirus disease 2019 patients in Pakistan

Abstract: This study aimed to evaluate perceptions of safety and preparedness among health workers caring for coronavirus disease 2019 (COVID-19) patients before and after a multi-professional simulation-based course in Pakistan. Health workers’ perceptions of preparedness, safety, and their willingness to care for COVID-19 patients were measured before and after they attended a simulation-based training course to prepare them to care for COVID-19 patients at Combined Military Hospital Landi Kotal Cantt, from March 1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
0
24
0
1
Order By: Relevance
“…found signi cant improvement in all domains of personal strengths among 1,415 hospital staff members [19]. 65.9% of the surveyed staff in our study were highly or fully engaged during the sessions in comparison to 3.2% for whom engagement was little and minimal; Khan and Kiani found that the participants in their simulation courses believed from the start that their colleagues who did not attend the course were less prepared to handle COVID-19 patients [24]. At the end of the course, this perception was strengthened.…”
Section: Discussionmentioning
confidence: 48%
“…found signi cant improvement in all domains of personal strengths among 1,415 hospital staff members [19]. 65.9% of the surveyed staff in our study were highly or fully engaged during the sessions in comparison to 3.2% for whom engagement was little and minimal; Khan and Kiani found that the participants in their simulation courses believed from the start that their colleagues who did not attend the course were less prepared to handle COVID-19 patients [24]. At the end of the course, this perception was strengthened.…”
Section: Discussionmentioning
confidence: 48%
“…In a COVID-19 simulation assessment, Cheung et al found significant improvement in all domains of personal strengths among 1,415 hospital staff members [(Cheung et al, 2020)]. 65.9% of the surveyed staff in our study were highly or fully engaged during the sessions in comparison to 3.2% for whom engagement was little and minimal, Khan and Kiani found that the participants in their simulation courses believed from the start that their colleagues who did not attend the course were less prepared to handle COVID-19 patients [(Khan and Kiani, 2020)]. At the end of the course, this perception was strengthened.…”
Section: Discussionmentioning
confidence: 79%
“…The number of submitted manuscripts has increased by 95% in 2020 (from 146 in 2019 to 285 as of December 25, 2020). JEEHP has also published some articles related to COVID-19, including an editorial [ 4 ], training materials [ 5 ], and a research article [ 6 ]. However, it is not fully evident how to interpret this increase in submissions.…”
Section: The Covid-19 Pandemic and The Educational Environmentmentioning
confidence: 99%
“…I am happy that this editorial may contribute to health personnel’s safety. Furthermore, guidelines for distancing in daily life [ 5 ], and multi-professional simulation-based training on perceptions of safety and preparedness [ 6 ] will be helpful to overcome the present pandemic conditions.…”
Section: Journal Metrics and Statisticsmentioning
confidence: 99%